Reinventing Backend Subsetting at Google: Designing an algorithm with reduced connection churn that could replace deterministic subsetting. - WARD, PETER; WANKADIA, PAUL; GULIANI, KAVITA (Communications of the ACM, 2023)
The article presents information on Google’s development and implementation of a new algorithm called Rocksteadier Subsetting, created in order to reduce connection churn and improve scalability. Properties of the new algorithm include good connection balance, no frontend churn, and good subset spread. The new algorithm balances the number of connections per backend task, yet it does have trade-offs such as increased complexity and higher resource utilization.